Neither too Classic nor too Exotic: One‐Electron Na⋅B Bond in NaBH3− Cluster. Issue 23 (1st May 2021) - Pino‐Rios, Ricardo; Inostroza, Diego; Tiznado, William
Abstract: It is here reported that the NaBH3 − cluster exhibits a Na⋅B one‐electron bond, a well‐established type of electron‐deficient bonding in the literature. The topological analysis of the electron localization function, at the correlated level, reveals that Na −, when approaching the bonding distance, fairly distributes its valence electron pair between two lobes. One of these electrons is used to bond with BH3, which participates through its boron empty p ‐orbital. Furthermore, the bonding situation of LiBH3 −, KBH3 −, MgBH3, and CaBH3 global minima structures are similar to that of NaBH3 −, extending the family of these new one‐electron bond systems with biradicaloid character. Abstract : A two‐centre one‐electron bond (2c–1e): Chemical bonding analysis using electron localization function (ELF), at correlated level, shows that the NaBH3 − cluster exhibits a Na⋅B 2c–1e bond.